2009
DOI: 10.1007/s00018-009-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid precursor protein and its homologues: a family of proteolysis-dependent receptors

Abstract: The Alzheimer's amyloid precursor protein (APP) belongs to a conserved gene family that also includes the mammalian APLP1 and APLP2, the Drosophila APPL, and the C. elegans APL-1. The biological function of APP is still not fully clear. However, it is known that the APP family proteins have redundant and partly overlapping functions, which demonstrates the importance of studying all APP family members to gain a more complete picture. When APP was first cloned, it was speculated that it could function as a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 180 publications
(228 reference statements)
1
99
0
11
Order By: Relevance
“…Subsequently, sAPP has been found to stimulate growth in both neuronal and epithelial cells, to influence neurite outgrowth and synaptogenesis in the nervous system, and to stimulate motility in epithelial cells (26,27). As an intact integral membrane protein, the structure of APP suggests similarity to membrane receptors (28), and recent data have suggested possible roles for APP as a cell surface receptor with signaling functions activated through cell-cell and cellextracellular matrix contacts (26) and through proteolysis (29).…”
mentioning
confidence: 99%
“…Subsequently, sAPP has been found to stimulate growth in both neuronal and epithelial cells, to influence neurite outgrowth and synaptogenesis in the nervous system, and to stimulate motility in epithelial cells (26,27). As an intact integral membrane protein, the structure of APP suggests similarity to membrane receptors (28), and recent data have suggested possible roles for APP as a cell surface receptor with signaling functions activated through cell-cell and cellextracellular matrix contacts (26) and through proteolysis (29).…”
mentioning
confidence: 99%
“…The exact biological function of APP and its paralogues is still unknown, although several different studies have shown involvement of APP in cell adhesion, neurite outgrowth, synaptogenesis, modulation of synaptic plasticity, and neuroprotection (reviewed in Ref. 2). Homo-and heterotypic cis interactions of APP family members have been detected (3).…”
mentioning
confidence: 99%
“…Moreover, the production of soluble Appa-RFP and Aplp2-RFP fusion proteins may compensate for the loss of the full-length Appa and Aplp2 proteins, similar to studies in mice (Weyer et al, 2011). The ligand binding and adhesive activity of the extracellular domain of APP is important for its role in synaptogenesis, cell adhesion, and neurite outgrowth, but the exact biological function remains unclear (Jacobsen and Iverfeldt, 2009). The secreted App-RFP proteins expressed by the zebrafish appa is22Gt and aplp2 is23Gt gene trap alleles isolated in our study will be useful for investigating further the biological function of APP.…”
Section: Appa-rfp and Aplp2-rfp Are Localized To Blood Vessels In Thementioning
confidence: 78%